ARIMA models for the analysis of earthquake data in Peru in 2017 - Risco Franco, Carlos (2017)
This project seeks to explore the phenomenon of earthquakes through the use of statistical tools, in this case to characterize and search for patterns of behavior of earthquakes, which have occurred in Peru in 2017; for this purpose, techniques such as Cluster Analysis and Time Series Models are used. First, the zones of greatest seismic activity have been identified and then their main characteristics have been found, as well as the interrelation between magnitude and depth. Apart from identifying the seismic zones, a small decreasing trend in the magnitude of earthquakes in Lima in the last three months has been observed. The data have been fitted to an ARIMA (1,1,0) time series model, which has been found to be significant, both at the national level and for Lima-Ica and Arequipa. Data from the Peruvian Geophysical Institute on its web page has been used. The most active area is the Arequipa area, followed by Lima.